2017
DOI: 10.3390/ma10121381
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Ingredient Proportions and After-Treatment of Laser Sintering Walnut Shell Composites

Abstract: To alleviate resource shortage, reduce the cost of materials consumption and the pollution of agricultural and forestry waste, walnut shell composites (WSPC) consisting of walnut shell as additive and copolyester hot melt adhesive (Co-PES) as binder was developed as the feedstock of selective laser sintering (SLS). WSPC parts with different ingredient proportions were fabricated by SLS and processed through after-treatment technology. The density, mechanical properties and surface quality of WSPC parts before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Yu et al took walnut shell powder of 58–96 μm as raw material to prepare WSPC powder, and verified the feasibility of using WSPC powder for SLS by single-layer sintering experiment [ 29 ]. Through the study of different material ratio, the mechanical properties of WSPC parts were improved [ 30 ], and it was determined that when the volume fraction of walnut shell powder reached 40%, the warping deformation of WSPC parts was minimum and the dimensional accuracy was highest [ 31 ]. WSPC powder with 40% walnut shell was used to conduct SLS test by using five-factor and four-level orthogonal experimental design method, and the optimal process parameters were determined by using comprehensive weighted scoring method [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al took walnut shell powder of 58–96 μm as raw material to prepare WSPC powder, and verified the feasibility of using WSPC powder for SLS by single-layer sintering experiment [ 29 ]. Through the study of different material ratio, the mechanical properties of WSPC parts were improved [ 30 ], and it was determined that when the volume fraction of walnut shell powder reached 40%, the warping deformation of WSPC parts was minimum and the dimensional accuracy was highest [ 31 ]. WSPC powder with 40% walnut shell was used to conduct SLS test by using five-factor and four-level orthogonal experimental design method, and the optimal process parameters were determined by using comprehensive weighted scoring method [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…We observed that many 3D printing processes need a post-processing step. For example, fused deposition method (FDM) applies vaporization [ 3 ] or coating [ 41 ] after printing to improve the surface finishing; the selective laser sintering (SLS) method applies a post-sintering step to increase density and enhance the mechanical strength of the printed parts [ 38 ]; the stereolithography (SLA) or digital light processing (DLP) technology has a post-curing step to maximize the material’s physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Selective laser sintering (SLS) is one of the mainstream 3D printing techniques, where parts are fabricated layer by layer using a laser without using a preform or a mold [ 10 , 11 , 12 ]; during processing using SLS, raw powder materials are normally not fully melted, which is different from selective laser melting where powders are generally fully remelted and then solidified [ 13 ]. Currently, SLS technology is widely studied and developed for additive manufacturing of polymers and metals, and various polymer and metal powders for 3D printing can be commercially purchased [ 10 , 14 , 15 ]. However, the dense ceramic parts fabricated by SLS have not yet been realized due to the high melting temperature, low or no plasticity and the low thermal shock resistance of ceramics [ 14 ].…”
Section: Introductionmentioning
confidence: 99%